The great escape - Rudnick, Elizabeth; Markus, Christopher; McFeely, Stephen (New York : Marvel, 2011)
American soldiers have been captured by HYDRA--an evil organization that wants to control the world--and only one man dares to attempt a rescue mission--super-soldier Captain America!
At head of title: Captain America, the first avenger.
"Marvel Studios."
"Based on the motion picture screenplay by Christopher Markus & Stephen McFeely."
Keywords: Captain America -- (Fictitious character) -- Juvenile fiction; Captain America -- (Fictitious character) -- Fiction; Superheroes -- Juvenile fiction; Superheroes -- Fiction; Adventure and adventurers -- Fiction; Superheroes -- Fiction